An Optical Pulse Shaping Scheme for Simultaneous Photonic Filtering and Digitizing Systems - Yiwei Sun; Guiling Wu; Sitong Wang; Wang Cheng; Jianping Chen (IEEE Photonics Journal, 2020)
The equivalent filter response in the simultaneous photonic filtering and digitizing system is determined by the temporal precision and duration time of optical pulses. To achieve narrow-bandwidth filter response at high central frequency, a pulse shaping scheme based on the time-frequency mapping and attenuation-delay coupling is presented. The effect introduced by attenuation-delay coupling is derived, and the method to search optimized parameters for target bandwidth, off-band suppression and central frequency is presented. Precise shaping of optical pulses with full width at half-maximum in sub-nanosecond order is realized in experiments, which can generate an equivalent filter with bandwidth of 0.93 GHz and central frequency of 39.9 GHz in the simultaneous photonic filtering and digitizing system.